Sodium alginate / lotus root starch / bagasse composite film as well as preparation method and application thereof

By combining sugarcane bagasse powder with sodium alginate and lotus root starch, a sodium alginate/lotus root starch/sugarcane bagasse composite film was prepared, which solved the problems of environmental pollution caused by plastic packaging and waste of sugarcane bagasse resources, and realized the development of degradable and edible composite films, which had application potential in the field of food preservation.

CN119899431APending Publication Date: 2025-04-29GUANGXI UNIV OF CHINESE MEDICINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510204170.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-01-09
Filing Date
2025-02-24
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing plastic packaging causes environmental pollution, and sugarcane bagasse has not been effectively utilized, resulting in loss of economic benefits.

Method used

A sodium alginate/lotus root starch/bagbastard composite membrane was developed, and a new composite membrane material was prepared by combining sugar cane bagasse powder with sodium alginate and lotus root starch.

Benefits of technology

The transformation of sugarcane bagasse into a degradable and edible composite membrane has been achieved, solving the problems of environmental pollution and resource waste, and at the same time demonstrating its application potential in the field of food preservation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899431A_ABST
    Figure CN119899431A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium alginate / lotus root starch / bagasse composite film and a preparation method and application thereof, and belongs to the technical field of food preservation, the composite film comprises the following raw materials: sodium alginate, lotus root starch, bagasse powder, glycerin, whey protein, cinnamon essential oil and water; the preparation method of the composite membrane comprises the following steps: uniformly mixing the sodium alginate, the lotus root starch, the bagasse powder, the whey protein, the glycerol and the water, then heating in a water bath, cooling to room temperature, then adding the cinnamon essential oil, and sequentially performing vacuum degassing and ultrasonic treatment to obtain a composite membrane liquid; pouring the composite membrane liquid on a glass plate, then soaking the glass plate in a calcium chloride solution, taking out the glass plate, washing, and drying to obtain the composite membrane. The composite film prepared from the raw materials according to the proportion is smooth in surface, the components have good intermiscibility, and the composite film has good moisture retention and pork decay inhibition capacity and is expected to be used as a substitute material of a traditional plastic preservative film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food preservation, and in particular relates to a sodium alginate / lotus root starch / bagasse composite film and a preparation method and application thereof. Background Art

[0002] In the field of food science, plastic has always been the preferred material for food packaging due to its low cost and good stability. However, with the development of the times, more and more consumers have improved their awareness of environmental protection, and the shortcomings of plastic have also been increasingly valued. The emergence of new edible and degradable composite packaging film materials has opened a new era in the field of food packaging. Its functionality is no less than that of traditional plastic packaging films, and it is expected to become a substitute for plastic packaging in the future.

[0003] Guangxi is the province with the largest sugarcane production in China. Sugarcane production is an industry that cannot be ignored. However, bagasse, the product of sugar extraction, has not been well utilized. In most cases, it is directly discarded, which greatly causes economic losses and environmental pollution. The current application of plastic packaging also causes environmental pollution problems. The emergence of degradable and edible composite films provides a new idea to solve this problem.

[0004] Therefore, there is an urgent need to provide a composite film using bagasse as raw material, which can not only use bagasse in the process of preparing the composite film to solve the problem of bagasse waste, but also develop a new type of composite film material for food preservation. Summary of the invention

[0005] In view of the above technical problems, the present invention provides a sodium alginate / lotus root starch / bagasse composite film and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] A sodium alginate / lotus root starch / bagasse composite film, comprising the following raw materials:

[0009] Sodium alginate, lotus root starch, bagasse powder, glycerin, whey protein, cinnamon essential oil and water.

[0010] Optionally, each 100 ml of composite membrane solution includes the following raw materials:

[0011] 3.0-4.0g sodium alginate, 2g lotus root starch, 0.6-1.0g bagasse powder, 1g whey protein, 1g glycerin, 50mg cinnamon essential oil, and the balance is water.

[0012] Furthermore, every 100 ml of the composite membrane solution includes the following raw materials:

[0013] 4.0g sodium alginate, 2g lotus root starch, 0.6 sugarcane bagasse powder, 1g whey protein, 1g glycerin, 50mg cinnamon essential oil, and the balance is water.

[0014] Optionally, the particle size of the bagasse powder is less than 200 mesh.

[0015] Further, the preparation process of the bagasse powder is:

[0016] Remove the skin and core of the remaining bagasse (the bagasse is obtained by squeezing the juice with the skin of sugarcane) after juicing, add distilled water until the surface of the bagasse is covered, and heat in a 70℃ water bath with stirring for 2h; then wash and drain the water;

[0017] The dried bagasse was added into a sodium hydroxide solution, magnetically stirred at 70°C for 2 h, and repeatedly rinsed with distilled water until the rinse liquid was transparent and the pH was lower than 8. The mixture was then dried and crushed to obtain bagasse powder with a particle size of less than 200 mesh.

[0018] Furthermore, the usage ratio of the bagasse to the sodium hydroxide solution is 1 g: 20 mL; and the mass concentration of the sodium hydroxide solution is 4%.

[0019] The second technical solution of the present invention:

[0020] A method for preparing a sodium alginate / lotus root starch / bagasse composite film comprises the following steps:

[0021] Sodium alginate, lotus root starch, bagasse powder, whey protein, glycerin and water are mixed evenly, then heated in a water bath, cooled to room temperature, cinnamon essential oil is added thereto, vacuum degassing and ultrasonic treatment are performed in sequence to obtain a composite membrane liquid;

[0022] The composite membrane liquid is poured onto a glass plate, and then immersed in a calcium chloride solution, taken out, washed, and dried to obtain the composite membrane.

[0023] Optionally, the water bath heating condition is: heating at 60-70° C. for 30 min.

[0024] Furthermore, the water bath heating temperature is 70°C.

[0025] Optionally, the vacuum degassing time is 20 min;

[0026] The ultrasonic treatment time is 15 min.

[0027] Optionally, the thickness of the composite film liquid on the glass plate is 1 mm.

[0028] Optionally, the mass concentration of the calcium chloride solution is 2.5%.

[0029] The third technical solution of the present invention:

[0030] The composite film is used in the field of meat preservation, preferably pork.

[0031] Compared with the prior art, the present invention has the following advantages and technical effects:

[0032] The invention prepares an SLB film (Sodium alginate / lotus root starch / bagasse composite film, SLB) by utilizing sodium alginate, lotus root starch and bagasse, wherein the components have good compatibility with each other and have outstanding preservation ability when applied to fresh pork, and is a new composite packaging film with good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0034] Figure 1 The process flow chart of preparing the composite membrane of the present invention;

[0035] Figure 2 This is a finished product picture of 200-mesh bagasse prepared in Example 1 of the present invention;

[0036] Figure 3 This is a picture of the composite film prepared in Example 1 of the present invention;

[0037] Figure 4 The surface scanning electron micrograph (a) and the cross-sectional scanning electron micrograph (b) of the composite film prepared in Example 1 of the present invention are shown;

[0038] Figure 5 This is the X-ray powder diffraction pattern of the composite film prepared in Example 1 of the present invention;

[0039] Figure 6 It is a line graph showing the effects of sodium alginate addition amount (A), film-forming temperature (B) and bagasse powder addition amount on tensile strength in the single factor test of the present invention;

[0040] Figure 7 This is a comparison chart of the effect of bagasse powder addition on the transparency of composite films;

[0041] Figure 8 This is a comparison chart showing the effect of sodium alginate addition on the transparency of the composite film;

[0042] Fig. 9 This is a comparison chart of the effect of film-forming temperature on the transparency of composite films;

[0043] Fig.10 This is a statistical chart of the weight loss rate of pork under different storage conditions;

[0044] Fig.11 This is a line chart showing changes in pork pH under different storage conditions. DETAILED DESCRIPTION

[0045] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0046] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0047] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0048] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0049] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0050] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0051] The raw materials used in the present invention are all purchased from the market. The raw materials used in the following examples, single factor experiments and orthogonal experiments are shown in Table 1.

[0052] Table 1

[0053]

[0054] The technical solution of the present invention is further illustrated by the following embodiments.

[0055] Example 1

[0056] like Figure 1 As shown, a method for preparing a composite membrane comprises the following steps:

[0057] (1) Preparation of bagasse powder

[0058] Peel the remaining bagasse after juicing, remove the core, wash it and place it in a beaker, add distilled water until the surface of the bagasse is submerged, heat it in a 70°C water bath for 2 hours, stir it continuously during the period, and take it out after completion and rinse it with distilled water continuously until the attachments on the surface of the bagasse are rinsed clean; drain the water, add a 4% sodium hydroxide solution in the ratio of bagasse: sodium hydroxide = 1g: 20mL, stir it magnetically at 70°C for 2 hours, and then rinse it repeatedly with distilled water until the rinse liquid is transparent and the pH is lower than 8. The cleaned bagasse is placed in a 60°C oven for drying, and the dried bagasse is crushed by a crusher and sieved with a 200-mesh gauze to obtain a bagasse powder with a particle size of less than 200 mesh (such as Figure 2 shown).

[0059] (2) Preparation of sodium alginate / lotus root starch / bagasse composite film

[0060] 21) Weigh 8g of sodium alginate and add it to a beaker containing 150mL of distilled water, stir evenly, add 1.2g of 200-mesh bagasse powder, 2g of whey protein, 4g of lotus root starch and 2g of glycerol, mix evenly and adjust the volume to 200mL. Place the membrane liquid in a 70°C (film forming temperature) water bath and heat it for 30min, stirring continuously during the period until all dissolved and mixed evenly, take it out and cool it to room temperature, filter it with a 20-mesh gauze, add 100mg of cinnamon essential oil, stir evenly, vacuum degas for 20min, and ultrasonically treat for 15min to obtain a sodium alginate / lotus root starch / bagasse composite membrane liquid, put it in a 4°C refrigerator and let it stand for 24h for fresh use.

[0061] 22) Take out the prepared membrane liquid from the refrigerator, place it at room temperature until the membrane liquid temperature returns to room temperature, pour the composite membrane liquid onto a clean glass plate, scrape off excess membrane liquid with a scraper with a thickness of 1 mm, and retain the membrane liquid with a thickness of 1 mm on the plate, soak the entire glass plate together with the membrane liquid in a 2.5% calcium chloride solution for 30 minutes, take it out and rinse it repeatedly with distilled water until the calcium chloride solution attached to the surface of the composite membrane is rinsed clean, dry (dry in a constant temperature and humidity chamber at 25°C and 50% humidity or dry it naturally), and then remove the film to obtain a sodium alginate / lotus root starch / bagasse composite membrane (such as Figure 3 The composite film was stored at 25°C and 80% relative humidity for subsequent index determination.

[0062] 1. Single Factor Experiment

[0063] Following the single variable principle, when one of the variables of sodium alginate, bagasse powder and temperature in Example 1 is changed, the other two variables are kept unchanged, and the remaining conditions and steps are prepared according to the method of Example 1. The gradient of the variable factors (per 100 mL of composite membrane solution) is set as shown in Table 2 below:

[0064] Table 2

[0065]

[0066] The finished composite membrane was cut into spindles with an outer width of 1.40 cm, an inner width of 1.00 cm, a total length of 5.00 cm, and an inner length of 3.00 cm. The peak load deformation and work done at break were measured using a texture analyzer (as shown in Table 4), and the tensile strength of the composite membrane was obtained by calculation. The experiment was repeated three times and the average value was taken. The tensile strength calculation formula is as follows:

[0067]

[0068] Wherein, TS is the tensile strength of the sodium alginate / lotus root starch / bagasse composite film, MPa; W is the work required for the sodium alginate / lotus root starch / bagasse composite film to break, J; X is the peak load-type variable when the sodium alginate / lotus root starch / bagasse composite film breaks, mm; d is the thickness of the sodium alginate / lotus root starch / bagasse composite film, mm; l is the width of the sodium alginate / lotus root starch / bagasse composite film, mm.

[0069] The thickness of the composite film is measured as follows: the thickness of 10 layers of the composite film obtained in Example 1 is measured using a vernier caliper to obtain the thickness D, and then the thickness of a single composite film is calculated using the following formula. The above experiment is repeated three times to obtain the average value, and the calculation formula is as follows:

[0070]

[0071] Wherein, d is the thickness of a single sodium alginate / lotus root starch / bagasse composite film, mm; D is the thickness of 10 stacked sodium alginate / lotus root starch / bagasse composite films, mm. The results are shown in Table 3:

[0072] Table 3 Composite film thickness measurement results

[0073]

[0074] It can be seen from Table 3 that the thickness of a single composite film is 0.1 mm (± 0.02 mm). It can be seen that this experimental method retains 1 mm of film liquid when laying the film. After the film is formed, due to the evaporation of water, the final film thickness will be 1 / 10 of the thickness of the film liquid retained when laying the film.

[0075] Table 4

[0076]

[0077] Figure 6 To control the change of tensile strength of sodium alginate / lotus root starch / bagasse composite film under different sodium alginate addition amounts, film-forming temperature and bagasse addition amounts, it can be seen from the figure that in the single factor experiment, the influence trend of sodium alginate addition amount, film-forming temperature and bagasse powder addition amount on the tensile strength of SLB composite film is basically the same, all showing that with the increase of sodium alginate addition amount, film-forming temperature and bagasse powder addition amount, the tensile strength of SLB film first increases and then decreases. Different conditions have different effects on the composite film, resulting in different changes in tensile strength. In every 100 ml of composite film liquid, when the sodium alginate addition amount is 2.5-3.5g, the tensile strength of SLB film gradually increases, and reaches the maximum when the sodium alginate addition amount is 3.5g. During this period, the change of tensile strength is more obvious. After the peak value, the tensile strength shows a downward trend with the increase of sodium alginate addition amount. The main reason is that the oxygen atoms in the two G units of sodium alginate react with Ca 2+ Complexation reaction occurs, Ca 2+It is sandwiched between two single molecular units to form a structure similar to an inlay. This cavity inlay structure can well wrap the composite membrane liquid, greatly improving the overall structural stability of the composite membrane. Therefore, the tensile strength of the composite membrane is related to the ratio of the membrane liquid volume to the embedded cavity generated by the cross-linking of sodium alginate. When the amount of sodium alginate added is less than 3.5g, the ratio of the composite membrane liquid volume to the embedded cavity volume is greater than 1. As the amount of sodium alginate added increases, the tensile strength of the SLB membrane increases accordingly. When the ratio of the composite membrane liquid volume to the embedded cavity volume is 1, it reaches the maximum, that is, when the amount of sodium alginate added is 3.5g, the composite membrane liquid completely fills the embedded cavity, and the prepared SLB membrane has the maximum tensile strength; as the amount of sodium alginate added continues to increase, the ratio of the composite membrane liquid to the embedded cavity is less than 1. At this time, the composite membrane liquid cannot completely fill the sodium alginate and Ga 2+ The cavities produced by cross-linking reduce the tensile strength of the SLB film. When the film-forming temperature of the composite film is 55-65°C, the tensile strength of the SLB film gradually increases, and reaches the maximum when the film-forming temperature is 65°C. After passing the peak value, the tensile strength decreases with the increase of the film-forming temperature. The main reason is that the lotus root starch particles have a structure of alternating crystalline and non-crystalline regions. The energy provided by heating destroys the weak hydrogen bonds in the crystalline micelle region, and the particles absorb water and swell, the crystalline region disappears, and dispersed in water to become a colloid. This phenomenon, called starch gelatinization, greatly affects the solubility of the composite film solution mainly composed of starch in the solution system. Therefore, the change of film-forming temperature will affect the tensile strength of the composite film to a certain extent. Therefore, before reaching the optimal gelatinization temperature, the tensile strength of the composite film increases with the increase of the gelatinization degree. After reaching the highest value, that is, exceeding the gelatinization temperature, the starch structure changes, thereby reducing the tensile strength of the composite film. When the amount of bagasse added was 0.2-0.8g, the tensile strength of the composite film showed an upward trend, and then began to decline, and showed a cliff-like change. The reason for this phenomenon may be that bagasse is an additional additive that is insoluble in water. When added in a small amount, it can thicken the composite film liquid, thereby improving the tensile strength of the composite film. However, when added to a certain amount, the tightly connected structure of the composite film becomes loose, and the composite film is more likely to break when subjected to lateral stress, and the overall mechanical properties are reduced.

[0078] 2. Orthogonal test

[0079] The optimal amounts of the three influencing factors obtained through single factor experiments are 3.5g sodium alginate addition, 0.8g bagasse addition, and 65°C film-forming temperature. The previous and next groups of data on the single factor level gradient table (Table 2) of each area of ​​the three data, namely, 3.0g, 3.5g, and 4.0g sodium alginate addition; 0.6g, 0.8g, and 1.0g bagasse addition; and 60°C, 65°C, and 70°C film-forming temperature, constitute the factor level table, as shown in Table 5 below:

[0080] Table 5

[0081]

[0082] The three factors and three levels in Table 5 form an orthogonal analysis table as shown in Table 6 below:

[0083] Table 6

[0084]

[0085] According to the combination of sodium alginate addition amount, bagasse addition amount and film-forming temperature in Table 6, sodium alginate / lotus root starch / bagasse composite film was prepared according to the method in Example 1 with other conditions unchanged, and the tensile strength of the composite film prepared from each combination formula was measured according to the above method. Each measurement experiment was repeated three times in parallel and the average value was taken. The best formula for preparing sodium alginate / lotus root starch / bagasse composite film was obtained by analysis, and verification experiments were carried out. The orthogonal analysis is shown in Tables 7-9.

[0086] Table 7 Orthogonal result analysis table

[0087]

[0088]

[0089] It can be seen from Table 7 that the tensile strength of the orthogonal experimental composite film is mainly distributed between 4-5MPa, and the results of the three groups Y3, Y4, and Y9 are more prominent, among which the tensile strength of Y4 is the smallest and the tensile strength of Y3 is the largest. In order to determine whether Y3 is the best solution for this experiment, it is necessary to verify it through orthogonal range analysis experiments. As shown in Tables 8 and 9:

[0090] Table 8 Range Analysis Table

[0091]

[0092] Table 9 Orthogonal validation experiment results analysis table

[0093]

[0094] Conclusion: From the above table, we can see that KA1>KA3>KA2; KB3>KB2>KB1; KC3>KC1>KC2. Therefore, the best process is A1, B3, C3, that is, Y3, with 0.6g sugarcane bagasse addition, 4g sodium alginate addition, and 70℃ film forming temperature. Under these conditions, SLB composite film was prepared for verification experiment, and the results are shown in Table 8; Table 9 shows that the results of the experiment are correct, and the best process conditions for preparing sodium alginate / lotus root starch / sugarcane bagasse composite film are 0.6g sugarcane bagasse, 4g sodium alginate, and 70℃ film forming temperature.

[0095] Table 10 is the orthogonal experiment mean square analysis table, F 0.05 (2, 2) = 19. As shown in Table 10, the F values ​​of the three factors from sources A, B, and C are all greater than F 0.05 (2, 2), that is, it is believed that the amount of sugarcane bagasse added, the amount of sodium alginate added and the film-forming temperature all have a significant effect on the experimental results.

[0096] Table 10 Mean square analysis table

[0097]

[0098]

[0099] Effect verification

[0100] 1. Composite membrane performance determination

[0101] 1. Composite film transparency test

[0102] 1.1 Effect of changes in influencing factors in single factor experiment on the transparency of composite films

[0103] The composite film produced in the single-factor experiment was laid flat on a plane with a pattern drawn on it, and the effect of various influencing factors on the transparency of the composite film was determined by observing the clarity of the pattern and the number of bubbles on the composite film.

[0104] Figure 7-9 This is a comparison chart of the effects of various influencing factors on the transparency of the composite film in the single factor experiment. Figure 7 It can be seen that as the amount of sugarcane bagasse added increases, the transparency of the composite film decreases, and changes are visible to the naked eye. Therefore, it can be preliminarily inferred that the amount of sugarcane bagasse added is negatively correlated with the transparency of the composite film and has a more significant impact. The reason for this phenomenon may be that the added sugarcane bagasse is a transparent light yellow powder. If too much is added, it will hinder the penetration of light, thereby causing the transparency of the composite film to decrease. Figure 8It can be seen that with the increase of sodium alginate addition, the transparency of the composite film has no obvious change. Therefore, it can be preliminarily judged that the addition of sodium alginate has no correlation or a small correlation with the transparency of the composite film. The product produced by the cross-linking of sodium alginate and calcium chloride is in a relatively transparent state. Therefore, when it is added to the composite film, it has no effect on the transparency of the composite film or has an insignificant effect. Fig. 9 It can be seen that as the film-forming temperature increases, the transparency of the composite film increases, and changes that can be observed by the naked eye occur. Therefore, it can be preliminarily inferred that the film-forming temperature is positively correlated with the transparency of the composite film and has a significant impact. The main reason for this phenomenon may be related to the gelatinization degree of starch and the dissolution of sodium alginate. The solubility of starch particles and sodium alginate is low at low temperatures, which will affect the transparency of the film after film formation. As the temperature rises, the gelatinization of starch intensifies, the sodium alginate is completely dissolved, and the solution becomes colloidal. At this time, the film has better transparency.

[0105] 1.2 Transparency test of composite film

[0106] The composite film prepared by the best ratio obtained by the orthogonal experiment (i.e., the composite film prepared in Example 1) was cut into a rectangle of 15×70 mm and attached to the surface of a cuvette. Its absorbance X was measured at a wavelength of 580 nm, and its transmittance was obtained by calculation. The degree of transparency of the composite film was judged by the transmittance. A blank cuvette was used as a control group. The calculation formula was as follows:

[0107] T=(0.1) X ×100%

[0108] Wherein, T is the transmittance of the sodium alginate / lotus root starch / bagasse composite film, %; X is the absorbance of the sodium alginate / lotus root starch / bagasse composite film at a wavelength of 580 nm.

[0109] 1.3 Determination of water vapor permeability coefficient

[0110] Use a beaker with an inner diameter of 32mm and an inner height of 48mm, pour 10mL of water into the beaker, seal the beaker mouth with a composite film and weigh it, then put the beaker into a desiccator containing dry silica gel (the silica gel in the desiccator must be placed in a 60℃ oven for 24h before the experiment), weigh the beaker again after 6h, and calculate the water vapor permeability coefficient of the composite film. The calculation formula is as follows:

[0111]

[0112] Where WVTR is the water vapor transmission rate of sodium alginate / lotus root starch / bagasse composite film, gm -1 Pa -1 S -1; W is the weight change of the cup, g; X is the thickness of the sodium alginate / lotus root starch / bagasse composite film, mm; A is the exposed area of ​​the sodium alginate / lotus root starch / bagasse composite film, m 2 ; t is the experimental time, s; ΔP is the vapor pressure difference on both sides of the composite membrane, which is (3.168KPa, 25℃).

[0113] 1.4 Determination of moisture content of composite membrane

[0114] The moisture content of sodium alginate / lotus root starch / bagasse composite film was determined according to the direct drying method in GB5009.3-2016. The moisture content of the sample was calculated as follows:

[0115]

[0116] Where X is the moisture content of sodium alginate / lotus root starch / bagasse, g / 100g; m1 is the mass of the weighing bottle and sample, g; m2 is the mass of the weighing bottle and sample after drying, g; m3 is the mass of the weighing bottle, g; and 100 is the unit conversion factor.

[0117] When the moisture content is ≥1g / 100g, the calculation result shall be rounded to three significant figures; when the moisture content is <1g / 100g, the calculation result shall be rounded to two significant figures.

[0118] Table 11 Analysis of light transmittance, water vapor transmission coefficient and water content of sodium alginate / lotus root starch / bagasse composite film

[0119]

[0120] As shown in Table 11 above, the light transmittance of the finished sodium alginate / lotus root starch / bagasse composite film is 9.57% (±0.6). Compared with the composite film focusing on permeability, the light transmittance of the sodium alginate / lotus root starch / bagasse composite film is poor. In order to enhance the mechanical strength of the sodium alginate / lotus root starch / bagasse composite film, opaque bagasse powder is added, which makes its light transmittance worse and its transparency decreases.

[0121] The average water vapor permeability coefficient of the composite film is 0.26 g·mm / m 2 h·kPa, has a smaller water vapor permeability coefficient, and therefore has better barrier to water vapor permeability.

[0122] 2. Composite membrane structure characterization

[0123] 1. Scanning electron microscopy (SEM)

[0124] At an accelerating voltage of 3 kV, the sample was subjected to gold spraying treatment, and the surface of the composite film prepared in Example 1 was observed at magnifications of 40 times, 1000 times and 2000 times, respectively, and the cross section of the composite film was observed at magnifications of 150 times, 1000 times and 2000 times.

[0125] Figure 4 This is a scanning electron microscope image of the composite film prepared in Example 1 of the present invention. Figure 4 As can be seen in Figure (a), the surface of the composite membrane is relatively flat in the electron microscope photographs at 40 times, 1000 times and 2000 times, and there are no obvious cracks and wrinkles. From the electron microscope scanning image of the composite membrane surface, it can be seen that the overall compatibility of the composite membrane is good. This may be because under the cross-linking effect of sodium alginate and calcium chloride, the embedded cavity formed successfully fixes the composite membrane liquid, so that the composite membrane liquid will not shift during the drying and solidification process; the added sugarcane bagasse powder particle size can be easily integrated into the composite membrane liquid and is well wrapped. In the film forming process, the sugarcane bagasse powder does not remain on the surface of the composite membrane. Under the effect of drying, the cross-linked particles formed by sodium alginate adhere to each other to form a membrane surface in contact with the outside world. Figure 4 As can be seen in Figure (b), the cross section of the composite membrane has granular substances and many gaps under the 150x magnification lens; under the 1000x and 2000x magnifications, it can be clearly seen that the granular substances have a relatively smooth surface. The granular spheres should be the membrane liquid balls formed by the cross-linking of sodium alginate and calcium chloride to wrap the composite membrane liquid, and the entire composite membrane is composed of a number of composite membrane liquid balls, so some cavities appeared during the drying process; but under the 1000x and 2000x lens, it can be found that the composite membrane liquid particles are completely embedded in the composite membrane, and the gaps only exist on the cross-sectional surface and do not penetrate into the composite membrane. The reason for this phenomenon may be caused by cutting during the sample preparation process. This may be because the composite membrane is added with sugarcane bagasse, which increases the overall brittleness, resulting in biscuit-like fractures when cutting.

[0126] 2. X-ray powder diffraction (XRD)

[0127] The XRD pattern was determined by X-ray powder diffraction from 2θ=10° to 2θ=60° at a rate of 5° / min, a current of 50 mA and a voltage of 40 kV.

[0128] Figure 5This is the X-ray powder diffraction pattern of the composite film prepared in Example 1. It can be seen from the figure that the composite film has two diffraction peaks, one strong and one weak, at 2θ=22.59 and 2θ=38.58, indicating that the composite film contains two crystal structures and is a semi-crystalline biopolymer. At the same time, the position of the diffraction peak measured for the composite film obtained by repetitive experiments has no obvious change, which means that the crystal structure formed by the composite film tends to be stable and is not easily decomposed by changes in the external environment.

[0129] 3. Effect of composite film on storage of fresh pork

[0130] 1. Processing of fresh pork

[0131] The purchased fresh pork tenderloin was processed in a clean bench to remove fat and connective tissue exposed to the external environment. The meat was evenly divided into small pieces and placed in glass culture dishes that had been sterilized by high pressure in advance. The pieces were randomly divided into a blank group, a PE plastic wrap group, and a sodium alginate / lotus root starch / bagasse composite film group. Except for experimental sampling, the meat samples were kept in a 4°C refrigerator for 8 days. Sampling tests were carried out on days 0, 2, 4, 6, and 8, and three groups of parallel samples were set up respectively.

[0132] 2. Weight loss rate

[0133] The pork samples were weighed at 0, 2, 4, 6, and 8 days, and the weight loss rate of the pork was calculated according to the following formula:

[0134]

[0135] Where N is the weight loss rate of pork; m1 is the initial mass of pork on day 0, g; m2 is the mass of pork at subsequent sampling, g.

[0136] The above experiments required that each experimental group of samples be repeated 3 times in parallel to take the average value.

[0137] 3. Pork pH

[0138] Pork samples stored for 0, 2, 4, 6, and 8 days were sampled respectively, 10 g was weighed, added into 100 mL of distilled water and stirred evenly, soaked for 30 min, and then centrifuged at 3000 r for 10 min, and the supernatant was taken to measure the pH with a pH meter.

[0139] 4. Data Analysis

[0140] The above experiment was required to be repeated three times. The experimental results were expressed using standard deviation and mean value. Origin2021 software was used for drawing. SPSS26.0 software analysis of variance (ANOVA) was used for significance analysis of the data. The statistical difference was as follows: the sample group was compared with the control group.

[0141] Depend on Fig.10 It can be seen that the weight loss rate of pork preserved by plastic wrap is lower than that of pork preserved by composite film, and the weight loss rate of pork preserved by composite film is lower than that of pork in the blank group directly in contact with air. The change in the weight loss rate of pork is mainly due to the evaporation of free water in pork, and secondly due to the respiration of pig cells after death. The weight loss rate of pork preserved by composite film was significantly lower than that of the blank group in the first measurement, indicating that the composite film has a relatively good ability to retain moisture in pork, but it has not reached the level of plastic wrap. The pH value is an important indicator for evaluating the freshness of pork during the preservation process. Low pH values ​​can lead to PSE meat or DFD meat, while high pH values ​​can cause meat samples to deteriorate, so it is important to monitor the pH value. During storage, meat pH values ​​between 5.8 and 6.2 are judged as primary freshness; between 6.3 and 6.6 are judged as secondary freshness; and those exceeding 6.7 are judged as spoiled meat. Fig.11 It can be seen that after the start of fresh-keeping storage, the pH of the pork stored in the composite film group and the plastic wrap group increased to varying degrees, and the pH of the plastic wrap group increased significantly faster than that of the composite film group. After the 6th day, the pork in the composite film group and the plastic wrap group began to rot, but the pork in the composite film group rotted less quickly than that in the plastic wrap group; while the pH of the blank control group decreased first and then increased after the experiment began. The above phenomenon may be because the moisture retention ability of the plastic wrap is stronger than that of the composite film, so more moisture remains in the pork during the same storage time, and more moisture also makes it easier for microorganisms on the pork to reproduce and more likely to cause the corruption of the pork. In addition, cinnamon meat is added to the composite film during the production process, which has the effect of inhibiting the growth of microorganisms; while the pH of the blank group decreased first and then increased. This is because in the early stage of storage, the respiration of the meat sample itself, the acid produced in the fermentation of anaerobic glycogen and acidic substances (such as lactic acid and phosphoric acid) ATP phosphorylation process is used for energy supply, resulting in a decrease in the pH value of the meat sample. However, as storage time increases, microbial activity causes proteins to be broken down into amine metabolites, resulting in an increase in the pH of meat samples.

[0142] in conclusion:

[0143] (1) The effects of sodium alginate, bagasse, and film-forming temperature on the tensile strength of the composite film were determined by the single element experimental method. Based on this, the optimal ratio and conditions for preparing the composite film solution were determined by orthogonal experiments. That is, 8 g of sodium alginate and 1.2 g of bagasse were required to prepare 200 mL of film solution, and a film-forming temperature of 70°C was required. The composite film prepared under these conditions had a tensile strength of 6.9 MPa, a light transmittance of 9.57%, and a water vapor permeability coefficient of 0.26 g·mm / m 2h·kPa, and the water content was 19.8%. SEM and XRD proved that the surface of the composite membrane was smooth and the components had good solubility.

[0144] (2) The study on the preservation ability of pork proved that the composite film has good moisture retention and the ability to inhibit pork spoilage. Although its moisture retention is not as good as that of plastic wrap, its ability to inhibit spoilage is worse than that of plastic wrap. It is expected to be used as a substitute for traditional plastic wrap.

[0145] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A sodium alginate / lotus root starch / bagasse composite film, characterized in that: Including the following ingredients: Sodium alginate, lotus root starch, bagasse powder, glycerin, whey protein, cinnamon essential oil and water.

2. The sodium alginate / lotus root starch / bagasse composite film according to claim 1, characterized in that: Every 100 ml of composite membrane solution includes the following raw materials: 3.0-4.0g sodium alginate, 2.0g lotus root starch, 0.6-1.0g bagasse powder, 1g glycerin, 1g whey protein, 50mg cinnamon essential oil, and the balance is water.

3. The sodium alginate / lotus root starch / bagasse composite film according to claim 2, characterized in that: Every 100 ml of the composite membrane solution includes the following raw materials: 4.0g sodium alginate, 2.0g lotus root starch, 0.6g bagasse powder, 1g glycerin, 50mg cinnamon essential oil, 1g whey protein, and the rest is water.

4. The sodium alginate / lotus root starch / bagasse composite film according to claim 1, characterized in that: The particle size of the bagasse powder is less than 200 meshes; the preparation process of the bagasse powder is: Add distilled water until the bagasse surface is covered, and then heat in a water bath at 70°C with stirring for 2 hours; then wash and drain the water; The dried bagasse was added into a sodium hydroxide solution, magnetically stirred at 70°C for 2 h, and then washed, dried and crushed to obtain bagasse powder with a particle size of less than 200 mesh.

5. The sodium alginate / lotus root starch / bagasse composite film according to claim 4, characterized in that: The dosage ratio of the bagasse to the sodium hydroxide solution is: 1 g: 20 mL; The mass concentration of the sodium hydroxide solution is 4%.

6. A method for preparing a sodium alginate / lotus root starch / bagasse composite film, characterized in that: The following steps are involved: Sodium alginate, lotus root starch, bagasse powder, whey protein, glycerin and water are uniformly mixed, then heated in a water bath, cooled to room temperature, cinnamon essential oil is added thereto, and vacuum degassing and ultrasonic treatment are performed in sequence to obtain a composite membrane liquid; The composite membrane liquid is poured onto a glass plate, and then immersed in a calcium chloride solution, taken out, washed, and dried to obtain the sodium alginate / lotus root starch / bagasse composite membrane according to any one of claims 1 to 5.

7. The method for preparing a sodium alginate / lotus root starch / bagasse composite film according to claim 6, characterized in that: The water bath heating condition is: heating at 60-70° C. for 30 min.

8. The method for preparing a sodium alginate / lotus root starch / bagasse composite film according to claim 6, characterized in that: The vacuum degassing time is 20 min; the ultrasonic treatment time is 15 min.

9. The method for preparing a sodium alginate / lotus root starch / bagasse composite film according to claim 6, characterized in that: The thickness of the composite film liquid on the glass plate is 1 mm.

10. Use of the sodium alginate / lotus root starch / bagasse composite film according to any one of claims 1 to 5 in the field of meat preservation.